Assessment in grazing of plant materials of Tithonia diversifolia (Hemsl.) collected in Cuba - Ruiz, Tom?s E.; Febles, Gustavo; Gonz?lez, J.; Achang, Geovanis (Cuban Journal of Agricultural Science, 2013)
In order to assess highlighted materials of Tithonia diversifolia an experiment was conducted for two years under dry conditions and simulated grazing. The materials were collected in the center-west of Cuba. A random block design with factorial arrangement and four repetitions was applied. The factors were: A) plant materials (3, 5, 10, 13, 16, 17, 23, 24 and25) and B) plantation distance (0, 75, 1.0 and 1.5 m). The grazing was conducted with dry cows and instantaneous stocking rate of 38 LAU/ha/d, with occupation time from one to two days, and that of resting from 35 to 70 d for the rainy and dry season, respectively. The leaf weight per plant was measured in DM grams; the weight of 100 leaves in GM g, the leaf yield in 5 m in DM kilograms and the percent of animals eating. There was interaction for the factors under study during the dry season. During that, the plant material 17 had the lowest weight of leaf per plant (P < 0.01) for any of the plantation distances. The highest value was achieved by the material 3 at 0.75 m. The leaf yield in 5 m (P < 0.001) was better in plant material 3, planted at 0.75 m between furrows and did not differ from the collection 17, and the highest in the materials 5, 23 and 24. There was no interaction between the factors under study in the rainy season. The distance between furrows at 1.50 m reached the highest yield (P < 0.001). The weight of 100 leaves GM and that of the leaf in 5 m had better performance (P < 0.001) in collections 3, 23 and 3, 10 and 23, respectively. The animals did not surpass 20 % of the grazing time (P < 0.01) for the materials 24 and 17, while the rest surpassed this value. The materials 10, 13 and 23 highlighted, with values next to 30 %. The increase of the distance between furrows (P < 0.01) increased the amount of animals eating. It is concluded that plant material 17 should not be used as grazing plant. Material 3 should be the one used for this purpose during the whole year and, in the rainy season, the materials 10 and 23, as well as the 24 in the dry one. The materials 5, 10, 13, 23, 24 and 25 reached an intermediate performance. The increase of the distance between furrows (0.75 vs 1.50 m) favored the amount of animals eating. The results show the possibility of having materials of tithonia collected in Cuba, for its grazing for bovines. At the same time, they suggest the use of other shrubs in silvopastoral systems. Key words: assessment, plantation distance, grazing, tithonia.